LITERASI NUMERASI DALAM PEMBELAJARAN TEMATIK SISWA KELAS ATAS SEKOLAH DASAR - Ryzal Perdana; Meidawati Suswandari (Absis: Mathematics Education Journal, 2021)
The purpose of this study was to describe numeracy literacy in the thematic learning of senior elementary school students. This writing is done through literature study. The object of this research is numeracy literacy and thematic learning. The research subjects were elementary school upper class students. The data collection tool in this research is to search journals contained in several electronic media such as digital libraries, the internet, through Google Scholar. The data analysis technique used in this study was annotated bibliography analysis. The results showed that numeracy literacy in thematic learning of upper grade students of elementary school Numeracy literacy in thematic learning of upper grade elementary school students can be done by providing stimulus to students. To stimulate student curiosity, the availability of facilities and infrastructure, the capacity of school residents, and the capacity of stakeholders, a numeracy literacy work program twice a week before learning hours takes place, a mathematics and non-mathematics teacher training for thematic learning based on numeracy literacy is held, and fostering love reading to students and learning experiences that are fun while stimulating the imagination.